2004
DOI: 10.1097/00054725-200407000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Determinants of Health-Related Quality of Life After Ileal Pouch Anal Anastomosis for Ulcerative Colitis*

Abstract: HRQOL of patients with UC and IPAA is determined not only by IPAA-related factors but also by anxiety and extraintestinal manifestations with associated musculoskeletal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
3
23
0
4
Order By: Relevance
“…However, in a study by Provenzale et al [28] the SF-36 has been proven reliable to evaluate HRQOL in IPAA patients. The validity of SF-36 in IPAA patients has also been shown in other studies [10,29].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…However, in a study by Provenzale et al [28] the SF-36 has been proven reliable to evaluate HRQOL in IPAA patients. The validity of SF-36 in IPAA patients has also been shown in other studies [10,29].…”
Section: Discussionsupporting
confidence: 69%
“…The scores were significantly higher in 6 out of 7 subscales, and so were the PCS and MCS scores. Several studies have reported HRQOL scores of IPAA patients similar to the general population [10, 12, 18, 22-24, 47, 52] or slightly lower than those of the general population [11,20,29,54].…”
Section: Discussionmentioning
confidence: 99%
“…43 Basal cortisol and cytokine levels were unrelated to the level of fatigue. 6,44 Worse fatigue scores were reported in patients with short bowel syndrome 45,46 and in patients with ilealanal pouch anastomosis for UC, 47 but a possible influence of the disease course itself is difficult to exclude in these patients. No significant difference in fatigue scores was found in patients with primary sclerosing cholangitis (PSC) and IBD relative to those with IBD alone.…”
Section: Discussionmentioning
confidence: 99%
“…6,43,49 Also, the contributing factor most frequently reported in the literature, active disease, was confirmed in the present study. 49,52,61,[63][64][65][66][67][68][69][70][71][72][73][74][75][76] Other factors described in the literature which unfavorably affect HRQoL in IBD were female gender 50,62,68,64 , corticosteroid 77,64,78 or immunosuppressive drug use, 78 hospitalization, 64 short bowel syndrome, 45,46 extraintestinal manifestations, 62,47,74,78 IBS-like symptoms, 60,79 and impaired coping behavior. [80][81][82][83] Factors positively influencing HRQoL in CD were use of immunosuppressives (after 1 year follow-up), 64 postsurgery situation, 50,84,85 adalimumab maintenance treatment (at week 56), 49 and having a partner …”
Section: Discussionmentioning
confidence: 99%
“…Häuser and colleagues 23 found that pouchitis had the greatest impact on the 'bowel' component of the German version of the Inflammatory Bowel Disease Questionnaire (IBDQ-D). There are other functional scores for patients with a pouch 24,25 .…”
Section: Discussionmentioning
confidence: 99%